The El Derecho student society and the emergence of scientific unionism in Central America, 1898–1904 - Silva Hernández, Margarita (2025)
This article examines the student movement that emerged from the Sociedad El Derecho, at the University of San Carlos de Guatemala, led by the Nicaraguan Salvador Mendieta at the dawn of the twentieth century. For this research, an extensive review of primary documentary and printed sources in various archives of Central America was carried out, which were analyzed using the historical method and prosopography to determine the social composition of the movement. In the development of the work, the participation of students in national politics as opponents of the authoritarian rulers of the time and their interest in applying the scientific principles of the Social Sciences to politics and the project of regional union is demonstrated. It is concluded that this movement is the precursor of the current of Central American scientific unionism, whose objective was to create a cultural unity through civic education that would promote Central American identity and provide spaces of power to young intellectuals considered individuals prepared to exercise power and transform the region into a strong, free and independent state.